2011
DOI: 10.1088/0964-1726/20/8/087002
|View full text |Cite
|
Sign up to set email alerts
|

Micro and nanofilms of poly(vinylidene fluoride) with controlled thickness, morphology and electroactive crystalline phase for sensor and actuator applications

Abstract: Poly(vinylidene fluoride), PVDF, thin films have been processed by spin-coating with controlled thickness, morphology and crystalline phases. The influence of the polymer/solvent mass ratio of the solution, the rotational speed of the spin-coater and the temperature of crystallization of the films on the properties of the material has been investigated. It is shown that high-quality films with controlled thicknesses from 300 nm to 4.5 μm and with a controlled amount of electroactive crystalline phases can be o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
105
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(121 citation statements)
references
References 18 publications
6
105
1
Order By: Relevance
“…First principle calculations by Bystrov et al have shown that interaction between molecular chains of PVDF leads to the orientation of each molecular dipole moment along one direction parallel to the chain plane. [35] It is noteworthy that although β-phase crystals do not have preferential orientation in PVDF films formed by phase inversion 15 or by drying in air; 12 the PVDF membranes obtained may still exhibit a certain degree of piezoelectric effect as shown by our results in Figure 3h. However, this aspect has been largely ignore in the literature with the porous PVDF films formed by phase inversion usually considered unsuitable for poling and electroactive applications.…”
mentioning
confidence: 69%
See 4 more Smart Citations
“…First principle calculations by Bystrov et al have shown that interaction between molecular chains of PVDF leads to the orientation of each molecular dipole moment along one direction parallel to the chain plane. [35] It is noteworthy that although β-phase crystals do not have preferential orientation in PVDF films formed by phase inversion 15 or by drying in air; 12 the PVDF membranes obtained may still exhibit a certain degree of piezoelectric effect as shown by our results in Figure 3h. However, this aspect has been largely ignore in the literature with the porous PVDF films formed by phase inversion usually considered unsuitable for poling and electroactive applications.…”
mentioning
confidence: 69%
“…[5] PVDF shows four significant crystalline phases α, β, δ and γ; [2,6] with the electroactive β-phase being utilized most frequently for the development of sensors, actuators [7,8] and microgenerators. [4,9,10] Owing to its importance, the formation of electroactive β crystalline phase has been intensively investigated through various routes, including melt casting, [15] solution deposition, [11] spin coating [12] and phase inversion. [13,14] While, the films or membranes formed by 2 melting/crystallisation are dominated by α-phase, [15] those obtained by spin-coating and further dried at temperature between 30-60 ºC are largely dominated by β-phase crystals.…”
mentioning
confidence: 99%
See 3 more Smart Citations